Studi Kelayakan Wisata Paddy Lagoon di Desa Bojongsari Kecamatan Bojongsoang Kabupaten Bandung - Annisya Nur Shabila; Said Bambang Nurcahya (Manajemen dan Pariwisata, 2026)
Paddy Lagoon is an innovative project in Bojongsari Village, Bandung Regency, which integrates the food and sustainable tourism sectors in response to global challenges of food, water, and energy availability. Capturing the 2025 food tourism trend, this project transforms underutilized agricultural land into a unique ecology-based tourism education center. With a concept of floating stilt houses above carp breeding ponds, Paddy Lagoon highlights ecological architecture that utilizes natural materials such as affordable yet aesthetically pleasing Borneo wood and bamboo. Functionally, the area is divided into three main zones, including 20 kiosks for culinary MSMEs, a closed VIP area, and supporting facilities such as sanitation areas and a prayer room. This project is more than just a culinary center; it serves as a catalyst for socio-economic development that creates business opportunities for the local community and increases the village's original income. Ecologically, the integration of fish farming under the main building serves as a means of education about the food and water cycle without disturbing the sustainability of the surrounding rice fields and hills.